From Adversaries to Allies: Source Criticism and the Antipas–Pilate Relationship in Luke 23:12 - Gousopoulos, Christina (The catholic biblical quarterly, 2024)
The focus of the present contribution is twofold: first, to offer a source-critical analysis of the alleged relationship between Herod Antipas and Pilate in Luke 23:12; and, second, to subsequently reinterpret the role of their reconciliation within the Lucan passion narrative (v. 12a). To extend Steven Mason's compelling argument of Luke's likely dependence on Josephus, I argue that the feud between the two authorities in v. 12b may have been inspired by or inferred from Luke's engagement with Antiquities 18 and Jewish War 2. I also maintain that, while Antipas and Pilate's reconciliation (and Antipas's involvement in the passion altogether) is probably a Lucan composition without a historical nucleus, their unexpected reconciliation in v. 12a importantly underscores one of the central tenets of the Lucan passion narrative. As Luke subtly urges for his audience, it is precisely the two authorities who were hostile to one another (and who had every reason to convict Jesus if he had proven to be insurgent) who find commonality in that which Jesus's own contemporaries and religious leaders fail to see: his innocence.